Profil Keluarga dan Angka Kejadian Stunting di Desa Tamedan Kota Tual Tahun 2023 - Wa Rina; Agnes Batmomolin; Notesya A. Amanupunnyo; Maritje F. Papilaya (Yayasan Pendidikan Penelitian Pengabdian Algero, 2023)
Stunting is a child who experiences impaired growth and development caused by prolonged malnutrition and recurrent disease, thus affecting the child's height and length (BPS, 2021). Data from SSGI in 2022 showed that the number of stunted children in Tual City was 24.9 percent. The results of our initial survey in Tamedan Village showed that there were 28 stunted toddlers, 4 LBW babies, 30 malnourished toddlers, 83 babies and toddlers who routinely conducted monthly growth and development checks, 3 mothers who gave birth too close together, and 1 unplanned or unwanted pregnancy. The implementation of this PkM activity was carried out in Tamedan Village, Tual City, the implementation time was in August 2023. The participants who participated in this activity were all mothers who had children under five years old, totaling 28 people. The methods we used in this community service activity included counseling and demonstrations on how to process nutritious food. PkM results: stunting can be prevented and overcome by the way mothers during pregnancy must consume or eat nutritious foods and mothers must remain healthy or in good condition. Parenting such as providing nutritious food that suits the needs of children can prevent stunting. Processing food in the right way can maintain food nutrition. Mothers in Tamedan Village gain additional knowledge about how to prevent stunting, know the right parenting patterns and how to process food properly.